PEMANFAATAN MICROSOFT WORD DALAM MENINGKATKAN EFEKTIFITAS PEMBELAJARAN DI SMK IBRAHIMY 1 SUKOREJO SITUBONDO - Lailatul Fitriyah; Lubebetun Nafisa; Zaehol Fatah (Jurnal Padamu Negeri, 2025)
The Microsoft Word training held on July 9-10, 2025, at SMK Ibrahimy 1 Sukorejo provides effective results by increasing the effectiveness of learning in the form of mastery of digital software. What is successful in this training is that it can train students with document processing skills in Microsoft Word to make it easier to complete assignments at school and prepare for technological knowledge in the world of work later. In training with an interactive and practical approach method, it increases students' creativity in making assignments or making proposals and other documents with good interaction in learning Microsoft Word. In terms of mastering its own features, making students with the features that have been given by this training can understand well, making students more confident in using Microsoft Word, and being able to compete in the field of school, and the world of work